Uterine Artery Doppler Velocimetry of Uterine Leiomyomas in Nigerian Women - Bukunmi Michael Idowu; Bolanle Olubunmi Ibitoye; Victor Adebayo Adetiloye (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective To describe the blood flow velocities and impedance indices changes in the uterine arteries of leiomyomatous uteri using Doppler sonography. Methods This was a prospective, case-control study conducted on 140 premenopausal women with sonographic diagnosis of uterine leiomyoma and 140 premenopausal controls without leiomyomas. Pelvic sonography was performed to diagnose and characterize the leiomyomas. The hemodynamics of the ascending branches of both main uterine arteries was assessed by Doppler interrogation. Statistical analysis was performed mainly using non-parametric tests. Results The median uterine volume of the subjects was 556 cm3, while that of the controls was 90.5 cm3 (p < 0.001). The mean peak systolic velocity (PSV), end-diastolic velocity (EDV), time-averaged maximum velocity (TAMX), time-averaged mean velocity (Tmean), acceleration time (AT), acceleration index (AI), diastolic/systolic ratio (DSR), diastolic average ratio (DAR), and inverse pulsatility index (PI) were significantly higher in the subjects (94.2 cm/s, 29.7 cm/s, 49.1 cm/s, 25.5 cm/s, 118 ms, 0.8, 0.3, 0.6, and 0.8 respectively) compared with the controls (54.2 cm/s, 7.7 cm/s, 20.0 cm/s, 10.0 cm/s, 92.0 ms, 0.6, 0.1, 0.4, and 0.4 respectively); p < 0.001 for all values. Conversely, the mean PI, resistivity index (RI), systolic/diastolic ratio (SDR) and impedance index (ImI) of the subjects (1.52, 0.70, 3.81, and 3.81 respectively) were significantly lower than those of the controls (2.38, 0.86, 7.23, and 7.24 respectively); p < 0.001 for all values. Conclusion There is a significantly increased perfusion of leiomyomatous uteri that is most likely due to uterine enlargement.